235U isotopic characterization of natural and enriched uranium materials by using multigroup analysis (MGA) method at a defined geometry using different absorbers and collimators - Yücel Haluk (Nukleonika, 2015)
Characterization of nuclear materials is an important topic within the context of nuclear safeguards, homeland security and nuclear forensics. This paper deals with the performance of multigroup gamma-ray analysis (MGA) method using the X- and γ-rays in the 80-130 keV region and enrichment meter principle (EMP) based on the analysis of 185.7 keV peak for a certain geometry using different absorbers and collimators. The results from MGA and those of EMP are compared. In particular, the effect of aluminum/lead absorbers and lead collimator on the enrichment determination of 235U in natural and low enriched samples is investigated in a given source-detector geometry. The optimum diameter/height ratio for the Pb-collimator is found to be Dc/Hc = 1.4-1.6 in the chosen geometry. In order to simulate the container walls, ten different thicknesses of Al-absorbers of 141 to 840 mg·cm-2 and six different thicknesses of Pb-absorbers of 1120-7367 mg·cm-2 are interposed between sample and detector. The calibration coefficients (% enrichment/cps) are calculated for each geometry. The comparison of the MGA and EMP methods shows that the enrichment meter principle provides more accurate and precise results for 235U abundance than those of MGA method at the chosen geometrical conditions. The present results suggest that a two-step procedure should be used in analyses of uranium enrichment. Firstly MGA method can be applied in situ and then EMP method can be used at a defined geometry in laboratory.